Impact of Hydrate Dissociation on the Stiffness and Strength of Hydrate Bearing Sands - Ayebazibwe, Derrick (Schulich School of Engineering, 2024)
The escalating global energy demand has propelled the exploration of unconventional energy resources, notably natural gas hydrates. These ice-like compounds, abundant in permafrost and marine sediments, harbor vast quantities of methane, a potent energy source. However, conventional methods for recovering methane gas from natural hydrate bearing sand (HBS) deposits requires dissociation of the hydrate, which has an impact on the mechanical stiffness and strength of the HBS. The safe and efficient production of methane from HBS reservoirs hinges on a comprehensive understanding of the intricate relationship between hydrate dissociation, hence reduction in hydrate saturation, and the mechanical behavior of the host sediments. This thesis investigates the impact of hydrate dissociation on the small-strain stiffness and shear strength of laboratory-synthesized methane hydrate-bearing sands. The excess gas method was employed to form methane hydrates within the sand specimens, simulating the conditions prevalent in many natural gas hydrate reservoirs. During hydrate formation and subsequent dissociation, resonant column tests were conducted to evaluate the changes in small strain stiffness and damping ratio that occurred. Triaxial shear compression tests were then conducted on each specimen, once a known volume of hydrate had been dissociated, to obtain their unique stress-strain response which was compared to the typical stress strain plot of intact hydrate bearing sand prepared exactly the same way and the stress strain plot of hydrate free host sands. The research findings reveal that hydrate formation significantly enhances the stiffness and strength of the sand, but dissociation, regardless of the method, leads to a substantial reduction in both properties. Notably, thermal stimulation causes a more rapid degradation of both mechanical properties compared to depressurization for the same degree of hydrate dissociation. The study also elucidates the distinct mechanisms governing the mechanical response of HBS ...